THE EFFECT OF CASH TURNOVER, RECEIVABLES TURNOVER, INVENTORY TURNOVER AND COMPANY GROWTH ON PROFITABILITY IN MANUFACTURING COMPANIES IN THE MULTIPLE INDUSTRIAL SECTORS LISTED ON THE INDONESIA STOCK EXCHANGE IN 2018-2020 - Vista, Vera; Leandra, Winson Augustin; Katharina, Ninta; Seliamang, Yunelci Martha (SULTANIST: Jurnal Manajemen dan Keuangan, 2023)
The decline of business income is one of the negative impact by the Coronavirus Disease Pandemic or we known as COVID-19 which attack all of the world included Indonesia. Company profitability can be affected by many factors of finance, which all are measured with finance ratio. This research intended to analyze the connection between cash flow, accounts receivable turnover, supply flow and company growth with manufacture company profitability at Industry sector on Indonesia Stock Exchange in 2018-2020. This analyze focus on industry company at Indonesia Stock Exchange in 2018-2020. 42 companies are selected as sample in this research with purposive sampling method. This research done with multiple regression analysis. According to the research, partially the results of the T test has negative connection and significant between profitability and cash turnover, accounts receivable turnover, and company growth also has positive connection and significant between profitability and inventory turnover title. Although with simultaneous the results of the F test, ROA simultaneously influenced significant by cash turnover, accounts receivable turnover, inventory turnover and company growth.